REALISM IN EDUCATION PERSPECTIVE: Epistemological and ontological conception ;Axiology of realism ; Realism in Education; - ZNuroh, Ermawati (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2020)
The sense of realism is that the object of the senses is real and alone without relying on other knowledge or mindfulness. In the epistemological perspective, the flow of realism is to declare that the understanding of the subject is determined or influenced by the object. Realism tends to perceive, reason as one of the few objects being entirely called nature and also the emphasis that the outside world stands alone and does not depend on the subject. The flow of realism states that one's knowledge is gained through sensation and abstraction. In regard to value, the view of realism states that values are absolute, timeless, but still follows applicable natural laws. Education is actually meant to be a study or study of scholarly discipline through which we get definitions and classifications. Demonstration in the laboratory is also plural as a method of learning that is considered very effective in transferring knowledge to students. The teacher's role is as a facilitator, giving a set of basic ideas, and then giving students the opportunity to practice the subject or teaching materials that are being performed.